2019
DOI: 10.3390/app9153103
|View full text |Cite
|
Sign up to set email alerts
|

Experiment Research on Micro-/Nano Processing Technology of Graphite as Basic MEMS Material

Abstract: Graphite is expected to be a common choice for basic microelectromechanical-system (MEMS) material in the future. However, in order to become a basic MEMS material, it is very important for graphite to be adapted to the commonly-used micro-/nanoprocessing technology. Therefore, this paper used a directly lithography and etching process to study micro-, /nanoprocessing on graphite. The results show that the graphite surface is suitable for lithography, and that different shapes and sizes of photoresist patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…At the macro scale, when the relative roughness is less than 5%, the effect of roughness is often neglected. However, in micromachines and MEMS, due to the micro-nano size, the ratio of surface area to volume increases significantly, so that the surface effect increases [5][6][7][8][9], and the effect of surface quality becomes very prominent. For example, Broer found that poor surface quality has a detrimental effect on the availability of stable equilibria of MEMS [10].…”
Section: Introductionmentioning
confidence: 99%
“…At the macro scale, when the relative roughness is less than 5%, the effect of roughness is often neglected. However, in micromachines and MEMS, due to the micro-nano size, the ratio of surface area to volume increases significantly, so that the surface effect increases [5][6][7][8][9], and the effect of surface quality becomes very prominent. For example, Broer found that poor surface quality has a detrimental effect on the availability of stable equilibria of MEMS [10].…”
Section: Introductionmentioning
confidence: 99%